STRATEGI MENINGKATKAN KINERJA BELAJAR MELALUI PROGRAM REMEDIAL DAN PENGAYAAN DALAM PROSES PEMBELAJARAN - Nia Andriana; Azima Rohatullayali; Siti Hardiyanti; Miftahul Najwa; Putri Nabila; Firda Mardatillah; Laysha Nuzzilla (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Learning success is an important indicator in achieving educational goals. However, not all students are able to achieve optimal learning mastery due to differences in abilities and learning styles. Therefore, teachers need appropriate learning strategies through remedial and enrichment programs to accommodate students’ learning needs. This study aims to examine the role of remedial and enrichment programs in improving students’ learning success. This study employed a Literature Review method with a descriptive qualitative approach. Data were obtained from relevant journal articles and books through the Google Scholar, Garuda, and DOAJ databases. The research stages included identification, selection, and analysis of 15 literatures related to remedial programs, enrichment, and learning success. The results of the study indicate that remedial programs help students achieve learning mastery through improvements in the learning process, while enrichment programs help develop conceptual understanding, creativity, and students’ critical thinking skills. In addition, the implementation of remedial and enrichment programs supported by learning assessment can improve the effectiveness and quality of learning. Therefore, remedial and enrichment programs are important strategies in improving students’ learning success. ABSTRAK Keberhasilan dalam proses pembelajaran merupakan indikator penting dalam mencapai tujuan pendidikan. Namun, tidak semua peserta didik mampu mencapai ketuntasan belajar secara optimal karena adanya perbedaan kemampuan dan gaya belajar. Oleh karena itu, guru memerlukan strategi pembelajaran yang tepat melalui program remedial dan pengayaan untuk mengakomodasi kebutuhan peserta didik. Penelitian ini bertujuan untuk mengkaji peran program remedial dan pengayaan dalam meningkatkan keberhasilan belajar peserta didik. Metode yang digunakan adalah studi literatur dengan pendekatan deskriptif kualitatif. Data diperoleh dari artikel jurnal dan buku yang relevan melalui database Google Scholar, Garuda, dan DOAJ. Tahapan penelitian meliputi identifikasi, seleksi, dan analisis 15 literatur yang berkaitan dengan remedial, pengayaan, dan keberhasilan pembelajaran. Hasil kajian menunjukkan bahwa program remedial membantu peserta didik mencapai ketuntasan belajar melalui perbaikan proses pembelajaran, sedangkan program pengayaan membantu mengembangkan pemahaman konsep, kreativitas, dan kemampuan berpikir kritis peserta didik. Selain itu, penerapan remedial dan pengayaan yang didukung asesmen pembelajaran mampu meningkatkan efektivitas dan kualitas pembelajaran. Dengan demikian, program remedial dan pengayaan menjadi strategi penting dalam meningkatkan keberhasilan belajar peserta didik.